Biomechanical Impact of the Sclera on Corneal Deformation Response to an Air-Puff: A Finite-Element Study - Nguyen, B. Audrey; Roberts, Cynthia J.; Reilly, Matthew A. (Frontiers in Bioengineering and Biotechnology, 2019)
Aim or Purpose: To describe the effect of varying scleral stiffness on the biomechanical deformation response of the cornea under air-puff loading via a finite-element (FE) model. Methods: A two-dimensional axisymmetric stationary FE model of the whole human eye was used to examine the effects varying scleral stiffness and intraocular pressure (IOP) on the maximum apical displacement of the cornea. The model was comprised of the cornea, sclera, vitreous, and surrounding air region. The velocity and pressure profiles of an air-puff from a dynamic Scheimpflug analyzer were replicated in the FE model, and the resultant profile was applied to deform the cornea in a multiphysics study (where the air-puff was first simulated before being applied to the corneal surface). IOP was simulated as a uniform pressure on the globe interior. The simulation results were compared to data from ex vivo scleral stiffening experiments with human donor globes. Results: The FE model predicted decreased maximum apical displacement with increased IOP and increased ratio of scleral-to-corneal Young’s moduli. These predictions were in good agreement (within one standard deviation) with findings from ex vivo scleral stiffening experiments using human donor eyes. These findings demonstrate the importance of scleral material properties on the biomechanical deformation response of the cornea in air-puff induced deformation. Conclusion: The results of an air-puff induced deformation are often considered to be solely due to IOP and corneal properties. The current study showed that the stiffer the sclera, the greater will be the limitation on corneal deformation, separately from IOP. This may have important clinical implications to interpreting the response of the cornea under air-puff loading in pathologic conditions.